On Some Recent Developments in Ulam's Type Stability - Nicole Brillouët-Belluot; Janusz Brzdęk; Krzysztof Ciepliński (Abstract and Applied Analysis)
We present a survey of some selected recent developments (results and methods) in the theory of Ulam's type stability. In particular we provide some information on hyperstability and the fixed point methods.